Neonatal exposure to potent and environmental oestrogens and abnormalities of the male reproductive system in the rat: evidence for importance of the androgen-oestrogen balance and assessment of the relevance to man. - Williams, K; McKinnell, C; Saunders, P; Walker, M; Fisher, J; Turner, K; Atanassova, N; Sharpe, M (2001)
The effects on reproductive tract development in male rats, of neonatal exposure to potent (reference) oestrogens, diethylstilboestrol (DES) and ethinyl oestradiol (EE), with those of two environmental oestrogens, octylphenol and hisphenol A were systematically compared. Other treatments, such as administration of a gonadotrophin-releasing hormone antagonist (GnRHa) or the anti-oestrogen tamoxifen or the anti-androgen flutamide, were used to aid interpretation of the pathways involved. All treatments were administered in the neonatal period before onset of puberty. The cellular sites of expression of androgen receptors (AR) and of oestrogen receptor-alpha (ERalpha) and ERbeta were also established throughout development of the reproductive system. The main findings were as follows: (i) all cell types that express AR also express one or both ERs at all stages of development; (ii) Sertoli cell expression of ERbeta occurs considerably earlier in development than does expression of AR; (iii) most germ cells, including fetal gonocytes, express ERbeta but not AR; (iv) treatment with high, but not low, doses of potent oestrogens such as DES and EE, induces widespread structural and cellular abnormalities of the testis and reproductive tract before puberty; (v) the latter changes are associated with loss of immunoexpression of AR in all affected tissues and a reduction in Leydig cell volume per testis; (vi) none of the effects in (iv) and (v) can be duplicated by treating with high-dose octylphenol or bisphenol A; (vi) none of the reproductive tract changes in (iv) and (v) can be induced by simply suppressing androgen production (GnRHa treatment) or action (flutamide treatment); and (vii) the adverse changes induced by high-dose DES (iv and v) can be largely prevented by co-administration of testosterone. Thus, it is suggested that many of the adverse changes to the testis and reproductive tract induced by exposure to oestrogens result from a combination of high oestrogen and low androgen action. High oestrogen action or low androgen action on their own are unable to induce the same changes.